Monitoring of the state of electromagnetic fuel injectors of gasoline engines with distributed fuel injection systems - G. N. Votinov; D. V. Maltsev; D. S. Repetsky (Вестник СибАДИ, 2021)
Introduction. Ensuring the trouble-free operation of road transport is one of the priority tasks. The functioning of the internal combustion engine, the most important unit, is impossible without the correct operation of the fuel injectors. A modern electromagnetic nozzle is a fairly reliable element of the engine, however, it can quickly fail when using low-quality fuel. Constant monitoring of the technical condition of the injectors with the help of builtin vehicle diagnostics systems will prevent such negative consequences as fuel overspending, the formation of harmful substances in the exhaust gases, deterioration of the traction and speed characteristics of the vehicle.Materials and methods. The research was carried out by the method of physical modelling, a laboratory stand was developed that simulates the operation of the engine fuel system. As an object, the Bosch 0280 158 996 nozzle was selected, which was controlled using an Arduino-based electronic unit. A series of one-factor experiments was carried out, according to the results of which the dependence of the pressure drop rate on the contamination of the nozzle was constructed.Results. The permissible standard of the pressure drop rate during the operation of the electromagnetic nozzle is determined, which allows unambiguously determining its technical condition (serviceable/not serviceable). An algorithm for checking injectors is proposed, as well as a method for its implementation on modern passenger cars.Discussion and conclusion. The obtained dependence qualitatively coincides with the results of studies by other authors. There is a successful experience of implementing such algorithms on modern cars. The implementation of the research results will allow timely detection of faulty (contaminated) electromagnetic injectors and prevent negative effects on both engine parts and the environment.